Variability of organic carbon content in bottom sediment of Pahang River Estuary, Pahang, Malaysia - Yunus, Kamaruzzaman; Abdurahman, Siti Waznah; Ong, Meng Chuan; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal (Asian Network for Scientific Information, 2009)

(untitled)
The percentage organic carbon content of 62 bottom estuarine sediment in Pahang river estuary were analyzed using the wet dichromate oxidation method. In this study, the organic carbon distribution ranged from 0.09 to 2.05%. The high concentration can be found near the Pahang river mouth while the low concentration occurred at upstream. The sediment particle size at the same transects were also measured with the dry sieving and laser diffraction method. The average concentration of organic carbon was 0.88% while the average grain size was 2.44 φ. In this study, the carbon organic showed a significant relationship with the mean size (p<0.05) with the organic carbon content increase with the increase of mean size values.